SCHOOL ACCREDITATION BUSINESS PROCESS IN NORTH SUMATERA IN 2024 - Harfiani, Rizka (Proceeding International Seminar of Islamic Studies, 2025)
This study aims to describe the business process in the implementation of school accreditation in North Sumatra. The implementation of School Accreditation is carried out by the National Accreditation Board for Early Childhood Education, Elementary Education, and Secondary Education, in the Province of Sumatra in 2024. The research method uses a qualitative approach with a narrative type. Data collection techniques using observation, documentation, and data searches sourced from key informants. The data analysis technique uses a descriptive method, and data validity testing by extending the research and increasing accuracy, because the data to be presented is accurate data that is the result of school accreditation in North Sumatra in 2024. The results of the study show that the accreditation process in North Sumatra has followed the established procedures, the target quota for accreditation in 2024 has also been achieved well, although many obstacles were faced, but in the end the accreditation process can be completed. The conclusion of this study is that by complying with the rules that have been set in the school accreditation business process, the implementation of accreditation in the province will be carried out properly and smoothly.